THE REACTION OF PERIPHERAL BLOOD VESSELS TO ANGIOTONIN, RENIN, AND OTHER PRESSOR AGENTS - Abell, Richard G. (The Rockefeller University Press, 1942)
1. Both renin and angiotonin in small doses cause constriction of the arterioles in the ears of normal rabbits, as seen directly with the microscope. Capillaries appear unaffected while venules exhibit slight or no constriction with small doses and moderate constriction with large doses. The flow of blood through the tissues is not reduced except when very large doses are administered. Tyramine and methylguanidine sulfate in isopressor amounts act somewhat similarly. 2. Isopressor amounts of epinephrine and pitressin, by contrast, elicit severe vasoconstriction of arterioles lasting longer than that due to angiotonin, and flow of blood is sharply reduced or abolished altogether. The degree of venular constriction was also greater, while the capillaries remained unaffected. 3. The vasoconstrictor action of angiotonin on peripheral vessels in moat chambers in normal rabbit's ears is indistinguishable from that of renin, except that it is more rapid.